2017
DOI: 10.1016/j.envres.2017.07.052
|View full text |Cite
|
Sign up to set email alerts
|

24-h Nitrogen dioxide concentration is associated with cooking behaviors and an increase in rescue medication use in children with asthma

Abstract: Exposure to nitrogen dioxide (NO2), a by product of combustion, is associated with poor asthma control in children. We sought to determine whether gas-fueled kitchen appliance use is associated with 24-hour indoor NO2 concentrations and whether these concentrations are associated with asthma morbidity in children. Children aged 5–12 years old with asthma were eligible. Mean 24-hour NO2 concentration was measured in the kitchen over a four-day sampling period and gas stove use was captured in time activity diar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 31 publications
1
11
0
1
Order By: Relevance
“…Most reviewed evidence, mainly from US studies, suggested that exposure to higher indoor NO 2 concentrations leads to symptoms in children with asthma, including chest tightness, shortness of breath, wheeze, cough, nocturnal symptoms, increased number of asthma attacks and inhaler use, and decreased forced expiratory volume in one second (FEV1) [63][64][65][66][67]. Children living in inner cities appeared to be at higher risk for the adverse effects of NO 2 given their relatively high indoor exposure [64], although increased risk of asthma morbidity also occurred at NO 2 concentrations common in urban and suburban homes [57].…”
Section: Health Effectsmentioning
confidence: 99%
“…Most reviewed evidence, mainly from US studies, suggested that exposure to higher indoor NO 2 concentrations leads to symptoms in children with asthma, including chest tightness, shortness of breath, wheeze, cough, nocturnal symptoms, increased number of asthma attacks and inhaler use, and decreased forced expiratory volume in one second (FEV1) [63][64][65][66][67]. Children living in inner cities appeared to be at higher risk for the adverse effects of NO 2 given their relatively high indoor exposure [64], although increased risk of asthma morbidity also occurred at NO 2 concentrations common in urban and suburban homes [57].…”
Section: Health Effectsmentioning
confidence: 99%
“…Both prenatal and postnatal maternal and paternal smoking have been associated with increased risk of wheeze (19); and SHS exposure has been associated with not only morbidity, but also with incident asthma (20). In a systematic review, findings regarding the impact of domestic fuel combustion were mixed (20), although increases in both indoor particulate matter (PM) and NO 2 (primarily associated with stove use) have been associated with pediatric asthma-related outcomes in multiple recent studies, including nighttime inhaler use (21), asthma symptoms, and medication use (22). NO 2 was also associated with incident asthma in a population-based birth cohort study (23).…”
Section: Home Environmentmentioning
confidence: 99%
“…NO 2 is generated by automobiles and gas heaters and cooking ranges. Recent studies have shown a link between NO 2 exposure and reduced lung function (3*, 4*), increased need for rescue medications (28), and elevated risk and severity of asthma exacerbations (9, 11, 29). Gaffin et al reported that for every 10 ppb increase in classroom NO 2 concentration, there was a 5% reduction in FEV 1 /Forced Vital Capacity (FVC) ratio; classroom NO 2 was inversely associated with Forced Expiratory Flow at 25–75% of lung volume (FEF 25- 75) in this study (3*).…”
Section: Introductionmentioning
confidence: 99%